PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KARAKTERISTIK TUJUAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN LINGKUNGAN KERJA NON FISIK SEBAGAI VARIABEL MODERASI (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
The purpose of this study is to analyze and provide empirical evidence about the influence of budgeting participation and budget goal characteristics on managerial performance with a non-physical work environment as moderation. Population variables in this study are all leaders and financial officers in private vocational schools in the city of Semarang listed in the structure of the division of school work in 2016 which amounted to 14 vocational high schools and each was taken by 3 people so that there were 42 respondents, while the sampling technique used the census method. Data analysis method used is Regression Moderation Analysis (MRA) Hypothesis 1 test results note that the value of t arithmetic = 3.012> t table = 1.694 with a number of significance = 0.003 t table = 1.694 with a significance value = 0.010 t table = 1.694 with a significance value = 0.026 t table = 1.694 with the number of significance = 0.032